Not a sound - Gudenkauf, Heather (Park Row Books, 2017)
When a tragic accident leaves nurse Amelia Winn deaf, she spirals into a depression that ultimately causes her to lose everything that matters: her job, her husband David, and her stepdaughter Nora. Now, two years later and with the help of her hearing dog, Stitch, she is finally getting back on her feet. But when she discovers the body of a fellow nurse in the dense bush by the river, deep in the woods near her cabin, she is plunged into a disturbing mystery that could shatter the carefully reconstructed pieces of her life all over again. As clues begin to surface, Amelia finds herself swept into an investigation that hits all too close to home. But how much is she willing to risk in order to uncover the truth and bring a killer to justice?